Conditions Of The Business World, Industry World, Working World Of Indonesian Tourism - Yanti, Dewi; Liyushiana, Liyushiana; Khadry, Muhammad (LPPM Universitas PGRI Sumatera Barat, 2023)
The tourism business world continues to grow in line with the development of tourism that accommodates all the needs of tourists visiting various tourist attractions. The purpose of this study is to develop various strategies to answer these needs both in increasing the number of entrepreneurs and workers in accordance with the needs of the business world, the industrial world and the world of work, especially in the tourism sector. This study uses a qualitative research approach where qualitative research as a scientific method is often used and implemented by a group of researchers in the field of social sciences, including education. The results obtained after conducting research in two interview quotes delivered by two informants from the Lake Toba Authority Implementing Agency, it can be said that the need for workers in the tourism sector in 8 Regencies Around Lake Toba is currently still high. However, to support the two statements above, a projection will be calculated based on four tourism business samples, namely, star hotels, non-star hotels, restaurants/eateries and Travel. Based on arithmetic calculations, the number of workers in the next five (5) years can be projected. In 2023 the number of workers in travel is estimated at 722 people. In 2024 it will increase to 766 people. In 2025, there were 827 people. In 2026, it increased to 902 people and in 2027, it increased to 1,010 people. The conclusion obtained from the research results can be seen in the projection of the number of special workforce data on travel in the next five (5) years, increasing by around 5% - 12% each year.